Efeito de diferentes substratos no desenvolvimento de mudas de acerola (Malpighia emarginata DC.) - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2022)
The acerola crop (Malpighia emarginata DC.) originates from the regions of the Caribbean Islands, located in Central America. This fruit plant has adapted satisfactorily in the Brazilian scenario, so that it was introduced in Brazil by the northeast of the country, more precisely by Pernambuco. Regarding the production of acerola seedlings, it becomes an extremely important factor for good fruit production, so seedlings with maximum quality and vigor are a priority, giving rise to plants with excellent agronomic characteristics that imply high productive yields. Substrate is defined as a tool that works as a means by which plants can grow outside of soil conditions. Given the context, this study aimed to evaluate the different development characteristics of acerola seedlings subjected to different types of substrates. The experiment was carried out in the nursery of the Federal University of Oeste do Pará (UFOPA) in the municipality of Santarém, Pará. The municipality has a hot humid climate, with an average temperature ranging from 25 to 28ºC, with an average rainfall of 1,920 mm (SILVA, et al. 2011) ). The acerola seedlings were obtained from sowing in plastic tubes with a capacity of 120 cm³, all with homogeneous substrate and 90 days after germination, the plants were transferred to seedling bags, where the treatments were applied. The design used was randomized blocks with 3 treatments and 10 replications, the treatments consisted of T1: 100% Organic Earth; T2: 50% Organic Earth and 50% Cattle Manure and T3: 75% Organic Earth and 25% Açaí Fiber. For all plots, the same amount of substrates (treatment) in the amount of 3.5 kg were added. The results obtained show that T1 presented an average of 20.19 cm of plant height (HP) lower than the other treatments, which obtained 25.68 cm and 28.45 cm for T2 and T3 respectively. Regarding the number of leaves (NF) the results were: T1 with 26.76 leaves; T2 with 35.74 leaves and T3 with 37.04 leaves, so that the greater the number of leaves, the better the photosynthesis process. The absolute stem growth rate (TCAC) also presented T1 with lower mean values with 15%, T2 with 45.35% and T3 with 48.75%. Regarding the absolute growth rate in stem thickness (TCAEC), T1 differed statistically from T2 and T3 with values of 7.5%, 11.28% and 11.46% respectively. The use of a substrate composed of 50% Organic Soil and 50% bovine manure presents better agronomic performance for the production of acerola seedlings, so the good averages with the use of açaí fibers should be taken into account, as they present good cost-effectiveness in the Amazon scenario.
Keywords: Acerola; Baixo Amazonas; Fruticultura; Produtividade; CNPQ:: CIÊNCIAS AGRÁRIAS